2014
DOI: 10.1530/eje-14-0135
|View full text |Cite
|
Sign up to set email alerts
|

THERAPY OF ENDOCRINE DISEASE: Antithyroid drug use in early pregnancy and birth defects: time windows of relative safety and high risk?

Abstract: Background: Antithyroid drugs (ATDs) may have teratogenic effects when used in early pregnancy. Objective: To review the association between the time period of ATD exposure in early pregnancy and the development of birth defects. Methods: We identified publications on birth defects after early pregnancy exposure to the ATDs methimazole (MMI; and its prodrug carbimazole (CMZ)) and propylthiouracil (PTU). Cases of birth defects after ATD treatment had been initiated or terminated within the first 10 weeks of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(61 citation statements)
references
References 43 publications
(84 reference statements)
3
50
0
8
Order By: Relevance
“…In this study, the highest relative risk was seen for various types of abdominal wall defects (Fig. 3), followed by skin defects (aplasia cutis), digestive (oesophageal and other atresias), eye, urinary tract, respiratory (choanal atresia), and circulatory (ventricular septum) defects (57,58).…”
Section: Therapy Of Graves' Disease and The Risk Of Birth Defectsmentioning
confidence: 54%
See 1 more Smart Citation
“…In this study, the highest relative risk was seen for various types of abdominal wall defects (Fig. 3), followed by skin defects (aplasia cutis), digestive (oesophageal and other atresias), eye, urinary tract, respiratory (choanal atresia), and circulatory (ventricular septum) defects (57,58).…”
Section: Therapy Of Graves' Disease and The Risk Of Birth Defectsmentioning
confidence: 54%
“…In recent years, large studies from Japan (55, 56) and Denmark (57,58) have shown that MMI/CMZ-associated birth defects are more common than anticipated, and may affect ~1/30 of children exposed to the drug in the weeks 6-10 of pregnancy. This is considerably below 10% of the effect of thalidomide, the prime drug example of teratogenicity (59), but still enough to raise serious concern.…”
Section: Therapy Of Graves' Disease and The Risk Of Birth Defectsmentioning
confidence: 99%
“…Such birth defects are observed in about 3% of the neonates, and some birth defects may be detected later, resulting in a total prevalence of about 6% at 2 years of age. It has, therefore, recently been suggested that the use of ATDs at 6-10 weeks of gestation should be limited as much as possible to decrease the risk of birth defects [15] .…”
Section: Treatmentmentioning
confidence: 99%
“…PTU and MMI/CMZ cross the placenta and are equally effective for treating hyperthyroidism in pregnancy. PTU is the most widely used during pregnancy, generally with a shift onto this drug from MMI/CMZ shortly before conception [15] . The fetus benefits directly from the maternal ingestion of these drugs, which cross the placenta and act on the fetal thyroid gland.…”
Section: Treatmentmentioning
confidence: 99%
“…PTU and methimazole have similar placental transfer kinetics (DiavCitrin et al 2002). Due to the fetal teratogenicity associated with methimazole (Laurberg and Andersen 2014), PTU is considered the first-line in the treatment of Graves' disease during pregnancy (Chattaway and Klepser 2007). PTU could, however, induce hepatitis in fetus (Taylor and Vaidya 2012) and sometimes, changing from PTU therapy after first trimester to methimazole is considered to be the optimum treatment during pregnancy (Taylor and Vaidya 2012).…”
Section: Discussionmentioning
confidence: 99%